Crystal structure of tetragadolinium hexaiodide monogermanide, Gd4I6Ge - Lukachuk M.; Mattausch Hj.; Simon A. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
Gd4GeI6, monoclinic, C12/c1 (no. 15), a = 19.315(2) Å, b = 12.101(1) Å, c = 13.531(1) Å, β = 97.545(8)°, V = 3135.2 Å3, Z = 8, Rgt(F) = 0.057, wRref(F2) = 0.094, T = 293 K.